Potential of Borojoa patinoi Cuatrecasas water extract to inhibit nosocomial antibiotic resistant bacteria and cancer cell proliferation in vitro. Issue 5 (16th April 2018) - Chaves-López, Clemencia; Usai, Donatella; Donadu, Matthew Gavino; Serio, Annalisa; González-Mina, Robert Tulio; Simeoni, Maria Chiara; Molicotti, Paola; Zanetti, Stefania; Pinna, Antonio; Paparella, Antonello
Abstract : Borojó is a fruit used in Colombian traditional medicine for its supposed healthy effects. Abstract : Borojó ( Borojoa patinoi Cuatrec.) is a fruit used in Colombian traditional medicine with supposed antihypertensive, antitumoral, diuretic, healing, immunological, anti-inflammatory and aphrodisiac effects. To explore the relative merits in terms of biological activities of borojó aqueous extract (BAE), we investigated in vitro its antimicrobial activity on nosocomial pathogenic and multidrug resistant (MDR) strains of Pseudomonas aeruginosa (6), Staphylococcus aureus (1) and Candida species (6), as well as its cytotoxicity on human conjunctive Wong–Kilbourne derivative (WKD) cells and Caco-2 cells from heterogeneous human epithelial colorectal adenocarcinoma. The bacteriostatic activity was observed overall on P. aeruginosa strains, as evidenced by the increase of the lag phase (43 hours) and reduction of the maximum growth rate detected using 187.5 mg BAE per mL. The bactericidal activity, instead, was observed at 375 mg BAE per mL. On the other hand, BAE showed an anti-proliferative effect against the Caco-2 cell line and was shown to be toxic on the WKD cell line at concentrations ranging from 0.05 to 187.5 μg mL −1 . The analysis of the phenolic fraction of the fruit aqueous extract (BAE) using UHPLC-MS/MS showed the presence of 26 compounds, with vanillic, syringic and o -coumaric acids as the most abundant. Among these molecules, 7.81 ng mL −1 luteolin and myricetin, singly tested, were able to reduce bacterial growth. To the best of our knowledge, we are unaware of any previous studies demonstrating the anti-bacterial activity of borojó aqueous extract against antibiotic resistant strains of P. aeruginosa, and its anti-proliferative effect against WKD and Caco-2 cell lines. The latter result offers a potential base for new interest and investigations in relation to colon carcinoma models and borojó fruit consumption, since in Colombia this fruit is consumed also for its supposed antitumoral effects.